THE EFFECTS OF STOCKING DENSITY ON THE GROWTH AND SURVIVAL RATE OF Ompok hypophthalmus REARED IN FISH CAGES - Mulyadi, Mulyadi; Abraham S, Marthin; Hasibuan, Nuraini (Fakultas Perikanan dan Kelautan Universitas Riau, 2011)
The research was conducted from April to June 2010, in the research pondsof the Fisheries and Marine Science Faculty, Riau University. The objectives ofthis research were to find out the effects of different stocking density on thegrowth and survival rate of the fish reared in cages. Fishes used in this study were9.5 to 10 cm in total length. There were 4 treatments applied, namely 130, 170,210, and 250 fish/m3 and 3 replications applied in each treatment. The fish mealused in this research was commercial pellets, ad libitum, and four times/ day.Results of ANAVA shown that different stocking density did not affect thegrowth and survival rate of the fish. The best stocking density was 170 fish/m3 asit is indicated by high daily growth rate (2.29% of BW), high FCR (44.11%) andhigh survival rate (100%). Water quality parameters during the research weregood, temperature 27-330C, DO 3.6-6.8 ppm, pH 5-6 and ammonia (NH3) 0.030-0.075 ppm.